Experimental prototype development and performance analysis of a small-scale combined cycle for energy generation from biomass. (September 2017) - Amirante, R.; De Palma, P.; Distaso, E.; La Scala, M.; Tamburrano, P.
Abstract: This paper presents a research activity aimed at exploiting combined cycles (gas turbine plants coupled with steam cycles) for small-scale energy generation from carbon-neutral biomass. Such a goal has never been achieved before, since combined cycles are generally suited only for large-scale applications and for clean fuels. In order to adapt combined cycles to small-scale energy generation using dirty fuels, the implementation of cost-effective and commercially available components is studied, such as the use of a turbocharger and a power turbine taken from the automotive industry. The ongoing realization of the first prototype of small-scale combined cycle is presented in this paper, providing a detailed description of both the plant architecture and the main components chosen. In addition, a commercially available tool (Cycle Tempo) is used to demonstrate the high feasibility and potential of the plant in terms of efficiency. To that end, different plant configurations are studied and the effects of losses on the plant performance are investigated in detail.